Analysis of the implementation of green hotel in Villa Kayu Raja Bali - Herini, Forida Ayu; Murni, Ni Gst Nym Suci; Sari, I Gusti Agung Mas Krisna Komala (Journal of Applied Sciences in Travel and Hospitality, 2024)
Green hotels use green practices to reduce environmental impacts and increase the sustainability of hotel operations, including saving energy, managing waste and waste, and building design. This study aims to determine the application of the green hotel in Villa Kayu Raja Bali. This research is useful to encourage the hospitality industry to adopt environmentally friendly measures for sustainability. The types of data in this study are primary data and secondary data. The data collection method was obtained through observation, interviews, and questionnaire distribution with a saturated sample of 32 employees as respondents and 2 informants. Data analysis techniques in this study use descriptive qualitative and quantitative. The results showed an application value of 2.94 that overall the application of green hotels in Villa Kayu Raja Bali has been implemented well. Indicators that have been well implemented are architecture, water conservation, implementing new methods of saving electrical and water energy, the environment in the building, guest rooms, places to eat, saving paper, materials that need to be washed grouped, green guest rooms, green food, and green training programs. The indicators that need to be improved are in new energy; utilizing new energy and renewable energy sources, implementing new methods of saving solar energy, and environmental protection tools, namely refrigerators and air conditioners without Freon.